Performance Analysis of Renewable Energy Resources in Rural Areas: A Case Study of Solar Energy - Justo, Jackson J.; Mushi, Aviti T. (Tanzania Journal of Engineering and Technology, 2020)
This paper presents an overview of the recent development trends of solar photovoltaic (PV) systems and the performance in the Tanzanian context. The two types of solar power generation that are considered in this paper are: i) solar PV systems and ii) concentrated solar power (CSP). The two are compared in terms of cost of energy and energy storage mechanism. Moreover, the effect of ambient temperature on the solar PV module is analyzed. In addition, a detailed analysis on using solar axis tracking to increase the power generation is also presented. The extent to which the cell surface temperature and orientation of the solar module which determine the power generation is modeled. Since Tanzania has the possibility to utilize the solar irradiance in the Coastal region to generate solar power, and therefore it is selected as the case study in this paper. Keywords: Concentrated solar power, Levelized cost of electricity, Solar photovoltaic system.